Signalling and the Valuation of Unseasoned New Issues Revisited - Krinsky, I.; Rotenberg, W. (Journal of Financial and Quantitative Analysis, 1989)
This paper provides further empirical evidence on the relation between entrepreneurial ownership retention and the initial value of unseasoned common shares. A Canadian data set is employed to estimate the various empirical specifications used in previous studies and to examine additional variables suggested by recent developments in the theoretical literature. The estimation is carried out using a more general procedure to correct for heteroskedasticity. In contrast to previous findings, the entrepreneurial ownership retention signal does not possess statistical significance in any of the models examined.